2022
DOI: 10.3171/2021.9.jns211373
|View full text |Cite
|
Sign up to set email alerts
|

Combined stereotactic radiosurgery and tyrosine kinase inhibitor therapy versus tyrosine kinase inhibitor therapy alone for the treatment of non–small cell lung cancer patients with brain metastases

Abstract: OBJECTIVE Whether combined radiation and tyrosine kinase inhibitor (TKI) therapy in non–small cell lung cancer (NSCLC) patients with brain metastases (BMs) and epidermal growth factor receptor (EGFR) mutations confers additional benefits over TKI therapy alone remains a matter of debate. The goal of this study was to compare outcomes between combined TKI therapy with stereotactic radiosurgery (SRS) versus TKI therapy alone in NSCLC patients with BMs and EGFR mutations. METHODS Consecutive cases of NSCLC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The addition of stereotactic radiosurgery (SRS) to EGFR-TKI therapy has been reported to improve intracranial tumor control and provide a potential benefit of preventing neurological deficits and seizures. [63] The combined use of Gamma Knife radiosurgery and EGFR-TKI was shown to have the most significant effect on prolonging survival time after SRS in patients with EGFR-mutant lung cancer and brain metastasis [64]. A prospective study showed that the supernatant of cerebrospinal fluid (CSF) in patients with EGFR-mutant NSCLC and leptomeningeal metastasis (LM) is a valuable specimen for EGFR mutation testing, demonstrating that the detection rates of EGFR mutations and T790M in cell-free DNA (cfDNA) of CSF were 68.8%, and 14.6%, respectively.…”
Section: Egfrmentioning
confidence: 99%
“…The addition of stereotactic radiosurgery (SRS) to EGFR-TKI therapy has been reported to improve intracranial tumor control and provide a potential benefit of preventing neurological deficits and seizures. [63] The combined use of Gamma Knife radiosurgery and EGFR-TKI was shown to have the most significant effect on prolonging survival time after SRS in patients with EGFR-mutant lung cancer and brain metastasis [64]. A prospective study showed that the supernatant of cerebrospinal fluid (CSF) in patients with EGFR-mutant NSCLC and leptomeningeal metastasis (LM) is a valuable specimen for EGFR mutation testing, demonstrating that the detection rates of EGFR mutations and T790M in cell-free DNA (cfDNA) of CSF were 68.8%, and 14.6%, respectively.…”
Section: Egfrmentioning
confidence: 99%
“…Chiou et al reported that combined therapy was superior to TKIs alone in terms of tumor control, but not overall survival. They also discussed the synergistic effects of combined therapy in cases of EGFR-positive NSCLC 7 . In 2016, Zhang et al reported no signi cant difference between TKIs alone and combined therapy in terms of median OS 24 .…”
Section: Combining Gkrs and Tkis For Egfr-mutant Patientsmentioning
confidence: 99%
“…Taken together, it appears that in EGFR mutant patients, GKRS is effective for local tumor control and TKIs is effective for overall survival and new brain metastasis. Thus, combining radiosurgery with TKIs should be the preferred treatment for EGFR-mutant patients 7,25,26 .…”
Section: Combining Gkrs and Tkis For Egfr-mutant Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracranial radiation therapy, such as whole brain radiotherapy (WBRT) and gamma-knife radiosurgery (GKRS), is the conventional approach to treating brain metastasis. Combining target therapies with GKRS or WBRT has been shown to promote intracranial tumor control beyond what can be achieved using the target therapy alone [11][12][13]. In one study on 280 patients with EGFR-mutated NSCLC and brain metastases, Chiou et al reported that in terms of cumulative tumor control, a combination therapy involving TKI plus GKRS outperformed TKI alone.…”
Section: Introductionmentioning
confidence: 99%